2017
DOI: 10.1055/s-0037-1606544
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Safety of Ventriculostomy Using Two Different Procedures of External Ventricular Drainage: A Single-Center Series

Abstract: The present data indicate that PNT has a similar safety profile in emergency situations in critically ill patients who need immediate treatment for acute hydrocephalus when compared with the conventional EVD procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 24 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…These landmarks are mainly Kocher's point, medial epicanthus or midpupillary line, and the external acoustic meatus [2][3][4]. Recently, multiple studies have reported relevant rates of malpositioned freehand EVDs between 3 and 60%, resulting in revision or reinsertion procedures in up to half of these cases [1,20,27]. Intracranial hemorrhage, CSF infections, and neurological deficits are additional complications that may be caused by EVD misplacement with either multiple puncture attempts or need of revision [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…These landmarks are mainly Kocher's point, medial epicanthus or midpupillary line, and the external acoustic meatus [2][3][4]. Recently, multiple studies have reported relevant rates of malpositioned freehand EVDs between 3 and 60%, resulting in revision or reinsertion procedures in up to half of these cases [1,20,27]. Intracranial hemorrhage, CSF infections, and neurological deficits are additional complications that may be caused by EVD misplacement with either multiple puncture attempts or need of revision [13,18].…”
Section: Introductionmentioning
confidence: 99%